The Role of Kindergarten Managers in Activating Community Participation from the Teachers' Point of View- A Field Study in Lattakia City - شيخ أحمد, نادين; لميس حمدي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the research is to know the role of kindergarten Managers in activating community participation from the point of view of kindergarten teachers in Lattakia City, and to know the differences between the average responses of the members of the research sample on the research questionnaire according to (training courses, scientific and educational qualifications, years' Experience). The research was applied to (170) teachers working in (16) private kindergartens in Lattakia city. A questionnaire was used to ask the teachers about the role of kindergarten directors in activating community participation, and using the descriptive approach.The results of the research showed that the role of kindergarten Managers in activating community participation came to a middle degree from the teachers’ point of view, and there are no differences in the teachers’ views about the role of kindergarten Managers in activating community participation according to the variable years of experience, and there are differences in the perspectives of the kindergarten Managers in activating community participation according to (training courses: in favor of teachers who underwent training courses and the scientific and educational qualification in favor of educational qualification diploma holders). Based on the extracted results, the researcher made several proposals, including encouraging cooperation and coordination between the kindergarten administration, parents, civil society organizations and international organizations concerned with community participation.